?CHEMICAL POLYMORPHISM IN ASTERACEAE - Rajalakshmi, R; Jose, Joseph (Biological Sciences - PJSIR, 2003)
The qualitative and quantitative composition of the essential oils of seven plants of asteraceae family were investigated. The essential oils were obtained by hydro-distillation of plants and analysed by Gas Chromatograph. The major essential oil components identified, broadly belong to monoterpenoids, sesquiterpeniods and caryophyllene were found to be common in all the investigated species.